Saints in Local Religiosity: Relationships among Them and Their Significance in the Context of Calendar Customs - Belaj, Marijana (2008)
The present research looks at the cult of patron saints in a community in the hinterland of the Croatian coast. It uses calendar customs and focuses on the non-institutional practices on the saints` days. This approach offers the possibility to identify different categories of saints, as well as their significance and interrelationships in religiosity.
ENG